1998
DOI: 10.1093/emboj/17.9.2526
|View full text |Cite
|
Sign up to set email alerts
|

CIDE, a novel family of cell death activators with homology to the 45kDa subunit of the DNA fragmentation factor

Abstract: DFF45 is a subunit of the DNA fragmentation factor (DFF) that is cleaved by caspase-3 during apoptosis. However, the mechanism by which DFF45 regulates apoptotic cell death remains poorly understood. Here we report the identification and characterization of two mammalian genes, CIDE-A and CIDE-B, encoding highly related proteins with homology to the N-terminal region of DFF45. CIDE-A and CIDE-B were found to activate apoptosis in mammalian cells, which was inhibited by DFF45 but not by caspase inhibitors. Expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
280
1
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 296 publications
(294 citation statements)
references
References 26 publications
(33 reference statements)
11
280
1
2
Order By: Relevance
“…Curiously, the first described function of CIDEs was promotion of apoptosis. FSP27, CIDEA, and CIDEB exert robust apoptotic activity upon ectopic expression in mammalian cells (5,8,11,13,17). CIDE proteins have a region of amino acid sequence homology in their NH 2 -terminal halves, termed the CIDE N domain, that is also present in the major proapoptotic nuclease DFF40 and its inhibitory partner protein DFF45 (11).…”
Section: Ms Smas CMmentioning
confidence: 99%
See 2 more Smart Citations
“…Curiously, the first described function of CIDEs was promotion of apoptosis. FSP27, CIDEA, and CIDEB exert robust apoptotic activity upon ectopic expression in mammalian cells (5,8,11,13,17). CIDE proteins have a region of amino acid sequence homology in their NH 2 -terminal halves, termed the CIDE N domain, that is also present in the major proapoptotic nuclease DFF40 and its inhibitory partner protein DFF45 (11).…”
Section: Ms Smas CMmentioning
confidence: 99%
“…CIDE proteins have a region of amino acid sequence homology in their NH 2 -terminal halves, termed the CIDE N domain, that is also present in the major proapoptotic nuclease DFF40 and its inhibitory partner protein DFF45 (11). A CIDE C domain, present in their COOH-terminal halves, is found only in FSP27, CIDEA, and CIDEB (11). Although the physiological role of CIDE-induced apoptosis remains undetermined, recent studies for FSP27, CIDEA, and CIDEB have greatly illuminated the role of endogenous CIDE proteins and indicate that they have crucial roles in lipid metabolism (14 -16, 24, 33, 42, 44).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The expression of several pro-apoptotic proteins was down-regulated at D1, including ASK1 (Ichijo et al, 1997), CIDE-B (Inohara et al, 1998), ES18 , Granzyme B (Darmon and Bleackley, 1998), NIP3 (Chen et al, 1997;Yasuda et al, 1998), and the P2X ATP receptor (Brake et al, 1994; Table 2). Paradoxically, expression of the antiapoptotic regulator, IAP-A (Goyal, 2001), decreased more than 50%, whereas expression of NIX (Chen et al, 1999), a pro-apoptotic Bcl-2 family member, increased approximately twofold in differentiating C2C12 cells (Table 2).…”
Section: Coordinate Regulation Of Cell Cycle Withdrawal and Apoptosismentioning
confidence: 99%
“…The cell death-inducing DNA fragmentation factor-␣ -like effector (CIDE) family, i.e., CIDEA, CIDEB, and CIDEC (CIDE-3 or fat-specifi c protein 27), was identifi ed initially as a group of factors that induces apoptosis in mammalian cells ( 32,33 ). Recent studies using mice defi cient in CIDE proteins suggested that this class of protein is closely related to energy balance and obesity (34)(35)(36)(37).…”
Section: Western Blot Analysismentioning
confidence: 99%